2019
DOI: 10.1159/000503609
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Exudative Activity of Choroidal Neovascularization in Age-Related Macular Degeneration by OCT Angiography

Abstract: <b><i>Purpose:</i></b> Based on exudative activity, choroidal neovascularization (CNV) in age-related macular degeneration (AMD) can be classified as “active” aCNV, pretherapied “silent” sCNV (i.e., a treatment-free interval &#x3e;12 weeks), or treatment-naïve “quiescent” qCNV. We evaluated the qualitative and quantitative optical coherence tomography angiography (OCTA) features of these CNV subgroups. <b><i>Methods:</i></b> The presence of small-caliber vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…In this study, we found that CNV lesions did not always match with the area of fluorescein leakage and the characteristics of CNV were also morphologically and quantitatively different according to the leakage status in FA. The size and morphology of CNV in OCTA were analyzed for conducting comparison between active and quiescent CNV or determining the response to anti-VEGF treatment [5,[9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found that CNV lesions did not always match with the area of fluorescein leakage and the characteristics of CNV were also morphologically and quantitatively different according to the leakage status in FA. The size and morphology of CNV in OCTA were analyzed for conducting comparison between active and quiescent CNV or determining the response to anti-VEGF treatment [5,[9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…was defined as the morphology of the peripheral margin of the CNV indicating the connection of adjacent vessels, such as an arcades or loops. For quantitative assessment of CNV, we used the validated and open-source software program AngioTool (v0.6a, National Cancer Institute, Center for Cancer Research, Bethesda, MD, USA) with the threshold parameters: 30 and 255, vessel thickness: 5, and removal of small particles: 80 in accordance with previous studies [11,16] . After optimizing the parameters, the software analyzed the various aspects of vessel network architecture as shown in Figure 1H and Figure 2H, which included: 1) explant area (the area occupied by the convex hull containing the vessels); 2) NV area (the area of the segmented vessels); 3) NV area percentage (percentage of NV area/explant area); 4) total number of junctions (number of junctions in segmented vessels); 5) total number of endpoints (the number of open-ended segments); 6) total length of the vessel (the sum of Euclidean distances between the pixels of all vessels in the image); and 7) mean lacunarity (vessel nonuniformity among all-sized boxes) [16][17] .…”
Section: Subjects and Methods Ethical Approvalmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the retinal vascular network was analyzed by AngioTool software (Center for Cancer Research, version 0.6a, 64 bits, October 2014) 36 as a plugin of Fiji (ImageJ version 1.48; Wayne Rasband, National Institute of Health, Bethesda, USA). 17 , 22 , 37 The OCTA and FA images of the SVP, IVP, and DVP for all treatment groups were transformed to equal sizes by Fiji covering the area of laser lesions before the assessment of the retinal vascular plexus using AngioTool. The average number of visualized retinal vessels was calculated as vessel density indicating the percentage of area occupied by vessels inside the explant area in OCTA and FA images.…”
Section: Methodsmentioning
confidence: 99%
“…14 In our previous natural history study, we attempted to determine whether anatomic changes could serve as harbingers of near-term exudation, as several groups had reported that morphological changes detected by OCTA imaging of previously treated MNV could reveal patterns of anatomic changes that appeared to predict near-term recurrent exudation. [15][16][17] We investigated the association between MNV size and the rate of change in lesion size measurements just prior to exudation, but no obvious association between lesion size and the onset of exudation was identified. Other ocular parameters that might predict impending exudation include changes in choriocapillaris (CC) perfusion around the MNV, vessel area density (VAD), vessel skeleton density (VSD), volumetric measurement of the associated PED, and surrogate measures of choroidal perfusion such as choroidal thickness (CT) and the density of the choroidal vascular volume, also known as the choroidal vascularity index (CVI).…”
mentioning
confidence: 99%